ECONOMIC DEVELOPMENT OR HIDDEN BANKRUPTCY - Dmitry S. Shkolin; Lidia I. Tolmacheva (Вестник Северо-Кавказского федерального университета, 2022)
This article is about real economic development and GDP increase, which can be hidden for external government and private banks debts. We offer new approach to find the real economic productivity, cleared from currency consumption.